An investigation into the relationship between the development of rotation of the hip motor control - Versfeld, Pamela Anne (Division of Physiotherapy, 2018)
Although the relationship between increased anteversion and abnormal motor control in children with cerebral palsy is well documented there are no published studies that look at the possible links between motor control and femoral anteversion in children without neurological deficits. Children with intoeing gait are reported to be clumsy; but this clumsiness is usually ascribed to the gait angle. The aim of this study, therefore, is to explore the possible relationship between detorsion of the femur during growth and the development of hip posture and movement. Hip internal and external rotation are commonly used as a clinical measure of anteversion of the femur. In this study the range of hip internal and external rotation (as a clinical measure of anteversion) was related to performance of motor tasks requiring control of the posture and movement of the hip. If the degree of femoral anteversion is linked to the development of motor control, the next step would be to investigate the effectiveness of exercise programmes on the process of detorsion of the femur in children with excessive medial femoral torsion.